1995
DOI: 10.1016/0921-4534(95)00359-2
|View full text |Cite
|
Sign up to set email alerts
|

Origin of intrinsic Josephson coupling in the cuprates and its relation to order parameter symmetry: An incoherent hopping model

Abstract: Experiments on the cuprate superconductors demonstrate that these materials may be viewed as a stack of Josephson junctions along the direction normal to the CuO 2 planes (the c-axis). In this paper, we present a model which de-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
62
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 44 publications
6
62
0
Order By: Relevance
“…Strong scattering the barrier region (i.e. non-momentum-conserving hopping) [9][10][11] or 'occupation modulated hopping' [24] would invalidate our results. We will argue below that the close correspondence between our results and data suggests that the usual band theory form of the hopping is the correct one.…”
Section: Comparison To Data and To Other Theoriesmentioning
confidence: 69%
See 3 more Smart Citations
“…Strong scattering the barrier region (i.e. non-momentum-conserving hopping) [9][10][11] or 'occupation modulated hopping' [24] would invalidate our results. We will argue below that the close correspondence between our results and data suggests that the usual band theory form of the hopping is the correct one.…”
Section: Comparison To Data and To Other Theoriesmentioning
confidence: 69%
“…The observed σ c for optimally doped and overdoped materials provides evidence against the alternative explanation of the c-axis conductivity advanced in [9][10][11]. In these works, the weak frequency dependence of σ c at T > T c is attributed to a strongly momentum nonconserving interplane coupling t ⊥ (p, p ′ ), due physically to strong scattering in the interplane barrier layers, rather than to a large value of an in-plane electron scattering rate Γ.…”
Section: Comparison To Data and To Other Theoriesmentioning
confidence: 83%
See 2 more Smart Citations
“…There are two basic prerequisites for superconductivity: pairing and longrange phase coherence, as secured by the interlayer coupling [2]. While pairing has been interpreted in terms of either phononic or nonphononic mechanisms [3,4], the interlayer coupling has been regarded as Josephson tunnelling [5], resonant tunnelling [6], or as a charge transfer (CT) between relevant atomic and molecular orbitals [7]. A path-integral analysis has shown that a (coherent) axial transport may result from the interaction of fermionic excitations with double-well potentials associated with apex oxygens [8].…”
Section: Introductionmentioning
confidence: 99%